The interplay between body mass index, motivation for food consumption, and noncommunicable diseases in the European population: A cross-sectional study - Marija Ljubičić; Marijana Matek Sarić; Tamara Sorić; Ana Sarić; Ivo Klarin; Boris Dželalija; Alan Medić; Ivo Dilber; Ivana Rumbak; Jasmina Ranilović; Maria Papageorgiou; Viktória Szűcs; et al. (PLoS ONE, 2025)
Introduction Consuming unhealthy foods in emotional states can increase body mass index (BMI), contribute to becoming overweight, and lead to the development of chronic diseases. This study aims to investigate the associations between BMI, emotional motivation for food consumption, and health outcomes. Materials and methods “The Motivations for Food Choices” (EATMOT) questionnaire was used to assess the emotional components of food consumption in 9,036 individuals from 12 European countries. The multivariate analysis included linear and logistic regression to examine associations between variables. Results Regression models confirmed associations between BMI, emotional motivation for food consumption (β = 0.13; p < 0.001), obesity (β = 0.35; p < 0.001), diabetes mellitus, and hypertension (β = 0.04; p < 0.001 for both). Using food as a coping mechanism for stress contributed to an increase in BMI [OR = 1.31 (95% CI 1.14–1.51); p < 0.001]. Emotional consolation was associated with a higher likelihood of an increased BMI [OR = 1.22 (95% CI 1.03–1.44); p = 0.020] and obesity [OR = 1.47 (95% CI 1.06–2.06); p = 0.022]. Participants with obesity had a greater likelihood of developing noncommunicable diseases, such as cardiovascular diseases [OR = 2.18 (95% CI 1.45–3.28); p < 0.001], diabetes mellitus [OR = 2.02 (95% CI 1.31–3.12); p = 0.001], hypercholesterolemia [OR = 1.62 (95% CI 1.13–2.32); p = 0.009], hypertension [OR = 1.85 (95% CI 1.36–2.52); p < 0.001], and gastric disorders [OR = 1.81 (95% CI 1.16–2.85); p = 0.010]. Conclusion These results underscore the need for targeted public health interventions that address emotional eating behaviors and promote healthier coping strategies to mitigate the risk of obesity and related health complications.